Inhibition of Tissue Matrix Metalloproteinases Interferes with Mycobacterium tuberculosis-Induced Granuloma Formation and Reduces Bacterial Load in a Human Lung Tissue Model - Parasa, Venkata R.; Muvva, Jagadeeswara R.; Rose, Jeronimo F.; Braian, Clara; Brighenti, Susanna; Lerm, Maria (Frontiers in Microbiology, 2017)
Granulomas are hallmarks of pulmonary tuberculosis (TB) and traditionally viewed as host-protective structures. However, recent evidence suggest that Mycobacterium tuberculosis (Mtb) uses its virulence factors to stimulate the formation of granuloma. In the present study, we investigated the contribution of matrix metalloproteinases (MMPs), host enzymes that cause degradation of the extracellular matrix, to granuloma formation and bacterial load in Mtb-infected tissue. To this end, we used our lung tissue model for TB, which is based on human lung-derived cells and primary human monocyte-derived macrophages. Global inhibition of MMPs in the Mtb-infected tissue model reduced both granuloma formation and bacterial load. The infection caused upregulation of a set of MMPs (MMP1, 3, 9 and 12), and this finding could be validated in lung biopsies from patients with non-cavitary TB. Data from this study indicate that MMP activation contributes to early TB granuloma formation, suggesting that host-directed, MMP-targeted intervention could be considered as adjunct therapy to TB treatment.